Tracking-related experiences of second-generation Asian Indian students in the USA - Banerjee, Dina; Bhattacharya, Akshaj Dev (Frontiers in Education, 2023)
While tracking is a powerful determinant of educational inequality, scholarship pays little attention to tracking-related experiences. Tracking-related experiences of students reveal their challenges and coping mechanisms. Consequently, one learns the fundamentals of the agency. This study focuses on tracking the experiences of second-generation Asian Indian students in the USA. Between educational and economic success and discrimination, Asian Indians constitute an interesting population to study tracking. With the help of 177 in-depth interviews and qualitative data analyses, we find that tracking-related experiences of second-generation Asian Indian students are characterized by a challenge that reflects discrimination featuring the Indian identity.